2003
DOI: 10.1128/jvi.77.2.1621-1625.2003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Viral Disease Control Strategy: Adenovirus Expressing Alpha Interferon Rapidly Protects Swine from Foot-and-Mouth Disease

Abstract: We have previously shown that replication of foot-and-mouth disease virus (FMDV) is highly sensitive to alpha/beta interferon (IFN-␣/␤). In the present study, we constructed recombinant, replication-defective human adenovirus type 5 vectors containing either porcine IFN-␣ or IFN-␤ (Ad5-pIFN␣ or Ad5-pIFN␤). We demonstrated that cells infected with these viruses express high levels of biologically active IFN. Swine inoculated with 10 9 PFU of a control Ad5 virus lacking the IFN gene and challenged 24 h later wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 21 publications
(12 reference statements)
7
107
1
Order By: Relevance
“…Because the infection does not interfere with the host genome, Adeasy system shows a low risk to induce alteration of the host DNA. Therefore, it has been wildly used to deliver gene expression (Chinsangaram et al, 2003;Wesley et al, 2004;Mascola et al, 2005). After its infection of MES23.5 cells, a significant increase in intracellular iron levels was observed, which is in agreement with other studies conducted in the COS-7 cells and CHO cells (Worthington et al, 2000;Zhang et al, 2000).…”
Section: Discussionsupporting
confidence: 78%
“…Because the infection does not interfere with the host genome, Adeasy system shows a low risk to induce alteration of the host DNA. Therefore, it has been wildly used to deliver gene expression (Chinsangaram et al, 2003;Wesley et al, 2004;Mascola et al, 2005). After its infection of MES23.5 cells, a significant increase in intracellular iron levels was observed, which is in agreement with other studies conducted in the COS-7 cells and CHO cells (Worthington et al, 2000;Zhang et al, 2000).…”
Section: Discussionsupporting
confidence: 78%
“…Thus far, we have demonstrated that inoculation of mice with VRP-GFP induced a strong protective antiviral response against FMDV which correlated with increased levels of IFN-␣ in serum. This is in accordance with the demonstrated antiviral and protective effect of type I IFN against FMDV in the natural host (4,9,10). To confirm the antiviral effect of IFN-␣ against FMDV in the mouse model, we treated groups of five mice with 10 4 U of muIFN-␣ followed by challenge with 5 ϫ 10 4 PFU of FMDV A24 at 4 or 18 h after treatment.…”
Section: Ib-rs-2 Cells Do Not Respond To Vrp-gfp Infectionmentioning
confidence: 72%
“…The pVEK replicon vector is based on the current investigational new drug (IND) VEE virus vaccine (TC-83) (18,23). The poIFN-␣ and GFP genes were PCR amplified from existing DNA plasmids (9,24). Each PCR product coded for XbaI restriction sites at the 5= and 3= end.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 2 more Smart Citations